Impacts of Conservation Incentives in Protected Areas : The Case of Bolsa Floresta, Brazil - Cisneros, Elias; Borner, Jan; Pagiola, Stefano; Wunder, Sven (World Bank, Washington, DC, 2019)
Incentive-based conservation is a promising approach to tropical forest conservation, including within multiple-use protected areas. Here we analyze the environmental impacts of Bolsa Floresta, a longstanding forest conservation program combining conditional household payments with livelihood-focused investments in 15 multiple-use reserves of Amazonas State, Brazil. We use grid-based data, nearest-neighbor matching, and panel data econometrics to compare forest-related program outcomes (deforestation, degradation, fires) with non-participating reserves. While post-treatment deforestation and degradation was negligible, this was already the case pre-treatment, since low-threat reserves had preferentially been targeted. We thus find only statistically insignificant additional conservation effects from implementation. No important heterogeneous treatment effects could be detected either. Our findings thus add to the growing evidence that spatial mis-targeting towards low-hanging fruits, that is disproportionally selecting low-threat forest conservation areas into programs, constitutes a prime cause for low additionality found in rigorous impact evaluations of incentive-based forest conservation initiatives.